(untitled) (Journal of Hama University, 2021)
The correlation between the FDI inflow into host countries and economic development has been subject to rigorous research for years. In theory, the causal relation between FDI and GDP growth can run in either direction. On the one hand, according to the “FDI-led growth hypothesis”, FDI inflows can stimulate growth for the host countries. On the other hand, according to the “market size hypothesis”, a rapid GDP growth creating new investment opportunities in the host country can also cause larger inflows of FDI. it is also possible that a causal relationship between FDI and economic growth does not exist, supporting the so-called “neutrality hypothesis”. The aim of this study is to explore the causality relationship between Foreign Direct Investment and economic growth in Syria. Toda-Yamamoto analysis was used in order to test the hypotheses about the presence of causality between Foreign Direct Investment and Economic Growth. The study, which used the Annuall data covering the period between 1990 and 2010, showed that FDI inflows does not, Granger cause economic growth in the long run in Syria and economic growth does not, Granger cause FDI inflows in the long run.